PERAN SOSIAL EKONOMI DAN BUDAYA DALAM PENINGKATAN KEPEDULIAN MASYARAKAT NELAYAN TERHADAP KEAMANAN LAUT PULAU - PULAU KECIL TERDEPAN - Chairil N. Siregar (Fakultas Seni Rupa dan Desain ITB, 2009)
The area of Riau Islands Province is approximately 251.810,71 km2 or 95, 79 % of sea and 10.595.41 km2 or 4.21 % of land and there are 2.408 islands including big and small islands in the province. As we know that the small islands of Riau Islands Province directly face Singapore and Malaysia. These outer small islands has a function as the ocean security and defense zone. In this province the social development has not been well programmed and the social changes go slowly. It is caused by social structure that is not for the fishermen. The lack of their fish net/trap, the lack of their fund, the more polluted fishing area, and the irregular climate changes cause the fishermen difficult to fulfill their needs.